1990
DOI: 10.1080/00288233.1990.10428455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clovers in dry hill country 4. Components of subterranean clover regeneration at Whatawhata, New Zealand

Abstract: Thecomponents of regeneration of nine subterranean clover (Trifolium subterraneum L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…At Ballantrae, 'Mt Barker' flowered only 6-9 days before 'Tallarook' , instead of an expected interval of 20--26 days (Suckling et al 1983;Collins et al 1984). Later than expected flowering of 'Mt Barker' was also recorded at Whatawhata in 1982 (Sheath & Macfarlane 1990b) whereas at other sites, such as Kaikohe (Rumball & Cooper 1990) the flowering date of 'Mt Barker' was more in line with expectations. The reasons for site-to-site variation in the flowering behaviour of 'Mt Barker' are unclear.…”
Section: Discussionsupporting
confidence: 67%
“…At Ballantrae, 'Mt Barker' flowered only 6-9 days before 'Tallarook' , instead of an expected interval of 20--26 days (Suckling et al 1983;Collins et al 1984). Later than expected flowering of 'Mt Barker' was also recorded at Whatawhata in 1982 (Sheath & Macfarlane 1990b) whereas at other sites, such as Kaikohe (Rumball & Cooper 1990) the flowering date of 'Mt Barker' was more in line with expectations. The reasons for site-to-site variation in the flowering behaviour of 'Mt Barker' are unclear.…”
Section: Discussionsupporting
confidence: 67%
“…on steep hill country, especially northern facing slopes, which have little clover in the pasture as a result of regular seasonal dryness (Sheath & macFarlane 1990), greater pasture responses are likely to be obtained from application of N rather than P fertiliser. however, a moderate soil P status will be required to support the grass responses to N fertiliser.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivars which possessed an open, erect habit during reseeding were vulnerable to grazing damage and appeared unsuitable to current management practices in steep hill country. A propensity of some cultivars to germinate following summer rains was also unacceptable when reseeding was low (Sheath & Macfarlane 1990). To achieve maximum herbage yields, densities in June should exceed 150--200plants/m 2 • There was little advantage in using cultivars from the subspecies yanninicum ('Trikkala' and 'Larisa') and brachycalycinum ('Clare').…”
Section: Discussionmentioning
confidence: 99%
“…Consistently lower subterranean clover densities in June indicated that 'Woogenellup', 'Clare', 'Nangeela', and 'Larisa' were the least suited cultivars to the experimental conditions at Whatawhata. These cultivars exhibited low reseeding ability and/or a propensity to "false strike" (Sheath & Macfarlane 1990).…”
Section: Regenerationmentioning
confidence: 99%